Ex utero intrapartum treatment (EXIT) for upper airway obstruction. Issue 2 (April 2017) - Butler, Colin R.; Maughan, Elizabeth F.; Pandya, Pranav; Hewitt, Richard
Abstract : Purpose of review: Improvements in the antenatal diagnosis of congenital malformations have led to increased detection of fetal airway obstructing lesions, and pediatric ear, nose, and throat surgeons are increasingly involved in these cases. Recent findings: This article outlines the typical range of pathology seen, the logistics in providing support for anticipated deliveries and the multidisciplinary management of complex airway cases. Summary: Traditionally, difficulty in obtaining a patent airway at delivery was a major factor in the dismal prognosis of these pregnancies. The ex utero intrapartum treatment procedure, which involves controlled partial delivery of the fetus whilst maintaining placental circulation, allows various airway maneuvers to be performed to secure the airway in a controlled fashion.